2018
DOI: 10.1186/s12889-018-5543-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in risk perceptions during the 2014 Ebola virus disease epidemic: results of two consecutive surveys among the general population in Lower Saxony, Germany

Abstract: BackgroundThe Ebola virus disease (EVD) outbreak 2014 received extensive news media coverage, which faded out before the outbreak ended. News media coverage impacts risk perception; it is, however, unclear if the components of risk perception (affective and cognitive responses) change differently over time.MethodsIn an online panel, we asked participants (n = 1376) about EVD risk perceptions at the epidemic’s peak (November 2014) and after news media coverage faded out (August 2015). We investigated worry (aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Various findings on epidemic such as Ebola and SARS have also shown that different kinds of noncompliance hampered the ability of governments and healthcare departments to work efficiently in dealing with the epidemics. 52,53 One of the reasons of this noncompliance as well as denial of severity of COVID-19 by religious scholars could be mistrust in government. Studies have shown that individuals who mistrusted in government were much less likely to abide by government-directed mechanisms formulated to deal with various epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Various findings on epidemic such as Ebola and SARS have also shown that different kinds of noncompliance hampered the ability of governments and healthcare departments to work efficiently in dealing with the epidemics. 52,53 One of the reasons of this noncompliance as well as denial of severity of COVID-19 by religious scholars could be mistrust in government. Studies have shown that individuals who mistrusted in government were much less likely to abide by government-directed mechanisms formulated to deal with various epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…7-11 However, these findings showed inconsistencies when researchers measured associations at different time of a public health emergency. 39 , 40 As risk perceptions are influenced by contextual factors, a looming threat causes risk perceptions to grow higher, especially when that threat is seen as uncontrollable or dreaded. 41 , 42 For example, Obenauer and colleagues found a decrease in perceived likelihood of infection from the peak to the end of the Ebola epidemic.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 For example, Obenauer and colleagues found a decrease in perceived likelihood of infection from the peak to the end of the Ebola epidemic. 40 Before the COVID-19 epidemic erupted in China, the whistleblower and news media described COVID-19 as a “SARS-like disease.” As China was stricken by the SARS epidemic in 2003, many Chinese citizens had high levels of risk perception toward such an infectious disease. 43 When the epidemic broke out, the government instituted a lockdown of Wuhan on Jan 23.…”
Section: Discussionmentioning
confidence: 99%
“…Support for incidents of overt hostility. Beyond non-compliance with public health recommendations, the current outbreak in Eastern DRC has witnessed acts of aggression toward health facilities and EVD response teams [21]. As a marker of sympathy or support for more extreme social resistance to control efforts, we evaluated respondents’ agreement with the statement “People are justified in resisting the EVD control efforts (e.g., throwing stones, destruction of hospital property, taking away infected bodies, or chasing away the vaccination team)” (5-point Likert scale).…”
Section: Methodsmentioning
confidence: 99%